2017
DOI: 10.1016/j.neuropharm.2016.10.020
|View full text |Cite
|
Sign up to set email alerts
|

DMSO modulates CNS function in a preclinical Alzheimer's disease model

Abstract: DMSO has a widespread use as a vehicle for water-insoluble therapeutic drug candidates but may also exert disease-relevant pharmacological effects by itself. However, its influence on the CNS has hardly been addressed. Here we examined the brain structure and function following chronic exposure to low DMSO dose at a paradigm with flawed synaptic connectivity in a preclinical transgenic mouse model for Alzheimer's disease (APP mice). DMSO treatment increased spine density in a region-specific manner in the hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 60 publications
2
35
0
Order By: Relevance
“…This shows that R-MO might have weak cognitive enhancing effects and it suggests molecular mechanisms that might be involved. Spatial memory modulating effects of DMSO have been reported in previous studies, ranging from enhancing effects at low doses [32,33] to impairing effects at high doses [34]. We could observe at least an acutely impairing effect of DMSO on spatial memory and synaptic plasticity, possible long lasting effects, however remain to be investigated.…”
Section: Discussionsupporting
confidence: 52%
“…This shows that R-MO might have weak cognitive enhancing effects and it suggests molecular mechanisms that might be involved. Spatial memory modulating effects of DMSO have been reported in previous studies, ranging from enhancing effects at low doses [32,33] to impairing effects at high doses [34]. We could observe at least an acutely impairing effect of DMSO on spatial memory and synaptic plasticity, possible long lasting effects, however remain to be investigated.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, there existed < 1% (< 0.01 mL/kg body weight) DMSO in the injected EpoB solution. In a latest report, DMSO treatment (1% in drinking water, maintained for 34 days) increased spine density on neurons in a region‐specific manner and displayed behavior influence in Alzheimer's disease model (Penazzi et al ., ). Our dosage is lower than that adopted in the paper.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies reported that SalB is an inactive metabolite of the KOR-selective agonist Salvinorin A [26, 28]. However, DMSO has been shown to be able to modulate central nervous system function [29]. To estimate this effect, we used the sham group that didn’t express designer receptors that could be affected by SalB/DMSO.…”
Section: Methodsmentioning
confidence: 99%